Price Regulations in a Multi-unit Uniform Price Auction - Anette Boom (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Inspired by recent regulations in the New York ICAP market, this paper examines the effect of price regulations on a multi-unit uniform price auction. General bid caps reduce the maximum price below the bid cap, but also the minimum potential market price below the cap. A bid cap only for the larger firms does not guarantee a market price below the cap. A sufficiently high bid floor only for relatively small firms destroys some or all pure strategy equilibria with equilibrium prices above the marginal costs. With a general bid floor this happens only with considerably larger bid floors.
Keywords: D44; D43; L13; 330